Reflections on the Last 50 Years of the Law and Law School - Hardie Boys, Sir Michael (Victoria University of Wellington Law Review, 2000)
This paper was presented as a lecture on "Capital Law School Day" organised by the New Zealand Institute of Advanced Legal Studies to mark the occasion of the centenary of the Faculty of Law, Victoria University of Wellington in 1999.